2014
DOI: 10.1074/jbc.m114.593178
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Putative G Protein-coupled Receptor (GPCR) Docking Site on GPCR Kinase 2

Abstract: Background: Activation of GRK2 requires interaction with agonist-occupied GPCRs.Results: Residues on the GRK2 N terminus and kinase domain extension collaborate to create a GPCR docking site.Conclusion: Three GRK subfamilies use similar determinants to create the putative docking site, but subtle differences may dictate selectivity.Significance: Mapping the GRK-GPCR interface is required to understand the mechanism and specificity of GRK activation, and, therefore, the regulation of GPCRs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 54 publications
0
42
0
Order By: Relevance
“…To understand how GRK2 may function in NIH/3T3 cells, we took advantage of previous studies that have mapped critical amino acid residues in GRK2 that are required for kinase activity, membrane recruitment, interaction with GPCRs, and binding to G protein subunits (3235) (Fig. 3A).…”
Section: Resultsmentioning
confidence: 99%
“…To understand how GRK2 may function in NIH/3T3 cells, we took advantage of previous studies that have mapped critical amino acid residues in GRK2 that are required for kinase activity, membrane recruitment, interaction with GPCRs, and binding to G protein subunits (3235) (Fig. 3A).…”
Section: Resultsmentioning
confidence: 99%
“…Often, the key contribution of GRKs in mediating the switch between G protein and barr engagement is overlooked when screening for or assessing biased drugs. Structural work investigating the mechanism of GRK5 activation by GPCRs and investigations of GRK2 activation (23,24) indicate that GRK activation is a key feature of GPCR signal transduction. Therefore, elucidating this and other mechanisms of selective G protein or barr pathway engagement will inform future efforts to design functionally selective GPCR therapeutics.…”
Section: Discussionmentioning
confidence: 99%
“…A notable study by Beautrait et al (23), showed both G protein-and GPCR-mediated components of GRK2 recruitment and mapped the residues on the N-terminus of GRK2 involved in mediating recruitment and/or phosphorylation. Indeed, recent structural work at the b2AR and GRK5 demonstrates that GRK5 activation occurs via a rearrangement of GRK5's RH/catalytic domain, which facilitates interaction between the GRK's catalytic domain and the GPCR's intracellular loops (24).…”
Section: Introductionmentioning
confidence: 99%
“…lower affinity binding to the kinase active site (46). The C-tail is thought to play a role in kinase domain closure and activation (47)(48)(49). Full ordering of the C-tail is seen in chain A of the GRK4␣ structure (Fig.…”
Section: Discussionmentioning
confidence: 99%